If it's not what You are looking for type in the equation solver your own equation and let us solve it.
13x-(5-3x)=5(3x-1)
We move all terms to the left:
13x-(5-3x)-(5(3x-1))=0
We add all the numbers together, and all the variables
13x-(-3x+5)-(5(3x-1))=0
We get rid of parentheses
13x+3x-(5(3x-1))-5=0
We calculate terms in parentheses: -(5(3x-1)), so:We add all the numbers together, and all the variables
5(3x-1)
We multiply parentheses
15x-5
Back to the equation:
-(15x-5)
16x-(15x-5)-5=0
We get rid of parentheses
16x-15x+5-5=0
We add all the numbers together, and all the variables
x=0
| x/2+4x-3=2 | | 40-2q=8 | | 9m^2−9m+1=0 | | 30x-7=2x+5 | | 40=2(12)+2w | | 3y+3=6y+15 | | 8^2+x^2=14^2 | | 8k^2−2k−6=0 | | 8k2−2k−6=0 | | 4y+12=2y+14 | | 96=80+5x | | 7p^2+3p=0 | | 34.6+4h~5=8.44 | | 96=80=5x | | 2p+52=14p-44 | | 3(2x+1=4x+9 | | 40-4q=8 | | 6s-58+s+97=180 | | 6s-58=s+97 | | (6/5)x+10=(2x-13) | | x-11=6x-81 | | 9(6x-11)=21 | | 13s-1=14s-3 | | 39-5r=19 | | 3w+-4=w+8 | | 25/x+4-7=2 | | x+24=11x-6 | | 8x=0.6 | | 262=-u+46 | | 2x-100=x-8 | | 3x=54.3 | | -u+29=206 |